Within-host evolution of Helicobacter pylori shaped by niche-specific adaptation, intragastric migrations and selective sweeps - Florent Ailloud (Nature Portfolio, 2019)
Helicobacter pylori, a bacterial pathogen that infects human stomachs, has high genetic diversity across hosts. Here, Ailloud et al. reveal genetic structuring of H. pylori populations among different stomach regions of individual hosts and find signals of genetic associations with stomach region.